Think sink, not source: how vertical farming’s potential is limited by crop breeding - Meeuws, Gertjan; Heeling, Daan; Mogollón, José M.; Erisman, Jan Willem; Behrens, Paul (Frontiers in Plant Science, 2025)
Vertical farming (VF) could play a role in addressing some global food challenges, yet it requires higher crop yields and lower costs to become viable at large scales. While reductions in capital intensity are required, the need for new cultivars has been largely overlooked. This is partially a result of common crop dynamic models: Energy Cascade Models (ECMs). ECMs derive yield estimates based on assimilate production from incoming energy only, neglecting a plant’s limitations in storing and transporting assimilates. However, VF crops often experience sink-limited as opposed to source-limited conditions. Here, we adapt the ECM into a Plant Balance Model (PBM) that includes sink-limited conditions and show that current VF crop yields for lettuce and tomato are already close to sink-limited conditions. Further improvements in VF lettuce yields from the literature (700 kg m−2 yr−1) would require an unprecedented 51% decrease in crop cycle time (6.8 days). We estimate potential lettuce and tomato yields at 330 and 369 kg m−2 yr−1, respectively. However, improving lettuce and tomato yields beyond 230 and 145 kg m−2 yr−1, respectively, would require temperatures that current genetics do not tolerate. By assessing the sink-limited nature of current VF cultivars using the PBM, we reveal that proactive breeding programs are essential and without them, yields may stagnate very soon and limit future scalability.